HIV-1 Tat and cocaine impact mitochondrial epigenetics: effects on DNA methylation. Issue 9 (2nd September 2021) - Doke, Mayur; Jeganathan, Venkatesh; McLaughlin, Jay P.; Samikkannu, Thangavel
ABSTRACT: Human immunodeficiency virus (HIV) infection and the psychostimulant drug cocaine are known to induce epigenetic changes in DNA methylation that are linked with the severity of viral replication and disease progression, which impair neuronal functions. Increasing evidence suggests that changes in DNA methylation and hydroxymethylation occur in mitochondrial DNA (mtDNA) and represent mitochondrial genome epigenetic modifications (mitoepigenetic modifications). These modifications likely regulate both mtDNA replication and gene expression. However, mtDNA methylation has not been studied extensively in the contexts of cocaine abuse and HIV-1 infection. In the present study, epigenetic factors changed the levels of the DNA methyltransferases (DNMTs) DNMT1, DNMT3a, and DNMT3b, the Ten-eleven translocation (TET) enzymes 1, 2, and 3, and mitochondrial DNMTs (mtDNMTs) both in vitro and in vivo . These changes resulted in alterations in mtDNA methylation levels at CpG and non-CpG sites in human primary astrocytes as measured using targeted next-generation bisulphite sequencing (TNGBS). Moreover, mitochondrial methylation levels in the MT-RNR1, MT-ND5, MT-ND1, D-loop and MT-CYB regions of mtDNA were lower in the HIV-1 Tat and cocaine treatment groups than in the control group. In summary, the present findings suggest that mitoepigenetic modification in the human brain causes the mitochondrial dysfunction that gives rise to neuro-AIDS.